Short-term venous stasis induces fibrinolytic activation but not thrombin formation - Rühl, Heiko; Müller, Jens; Wäschenbach, Jana; Oldenburg, Johannes; Pötzsch, Bernd; Dewald, Oliver (Journal of Atherosclerosis and Thrombosis, 2014)
Aim: Venous stasis is a well-known risk factor for the development of venous thromboembolism. It is likely that stasis increases the risk of thrombosis by inducing hypercoagulability via the hypoxic procoagulant activation of endothelial and mononuclear cells and the accumulation of activated clotting factors. However, increased rates of thrombin formation have not been demonstrated in response to venous stasis in vivo.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Fibrinolysis; Thrombin; Vascular endothelial function